PENERAPAN DIGITAL GAME BASED LEARNING PADA GAME EDUKASI BELAJAR HURUF HIJAIYAH UNTUK ANAK TUNARUNGU (Studi Kasus: Yayasan Dharma Bhakti Kesejahteraan Sosial Provinsi Bengkulu) - iffan 29; Desi Andreswari; Ernawati Ernawati (Rekursif: Jurnal Informatika, 2026)
This study aims to design and develop an educational game based on Android using the Digital Game-Based Learning (DGBL) approach as a learning medium for Hijaiyah letters for hearing-impaired children. These children face challenges in understanding audio-based materials, such as Hijaiyah letters, which are typically taught through conventional methods. Therefore, a visual and interactive approach is needed to enhance their interest and comprehension. The research employs the ADDIE development model, consisting of Analyze, Design, Development, Implementation, and Evaluation stages. The application was developed using Hijaiyah material based on the Iqra’ method by As’ad Humam and integrated with visual hand sign language. It was tested on students at Yayasan Dharma Bhakti Kesejahteraan Sosial, Bengkulu Province. The evaluation involved pre-tests, post- tests, and usability testing using the System Usability Scale (SUS). The results showed a significant improvement in students’ understanding of Hijaiyah letters after using the game. Media feasibility scores reached 88% by media experts and 92% by subject matter experts. Thus, the DGBL-based educational game is considered feasible as an alternative learning medium for hearing-impaired children.